2015
DOI: 10.1055/s-0035-1556979
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge and factors related to acceptance of influenza vaccine by pediatric healthcare workers

Abstract: The aim of this study was to identify factors that affect influenza vaccination in order to devise means to increase compliance. In February 2003, pediatricians attending a national medical conference and nurses in a university hospital in central Israel were asked to complete a questionnaire regarding occupational data, knowledge issues, and reasons for undergoing/not undergoing vaccination themselves. Physicians also reported their practice of recommending the vaccine. A total of 181 physicians and 217 nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…23 As a vaccine against SARS-CoV-2 is not yet available, vaccination against seasonal influenza, which is recommended in many locations is crucial in preparing for the near future, 16,24,25 although vaccine hesitancy is a complex problem. 26,27 In conclusion, based on our findings, it is recommended to administer the influenza vaccine before the influenza season. This will reduce the burden of influenza, the widespread circulation of influenza strains, and is critical in scenarios of outbreaks or even increased incidence of both influenza and SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 66%
“…23 As a vaccine against SARS-CoV-2 is not yet available, vaccination against seasonal influenza, which is recommended in many locations is crucial in preparing for the near future, 16,24,25 although vaccine hesitancy is a complex problem. 26,27 In conclusion, based on our findings, it is recommended to administer the influenza vaccine before the influenza season. This will reduce the burden of influenza, the widespread circulation of influenza strains, and is critical in scenarios of outbreaks or even increased incidence of both influenza and SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 66%
“…Upon consent, 213 participants were instructed to complete a 30-question survey asking about their usage and perception of health information available on social media, its reliability, and its influence on their compliance to vaccinate against influenza (see Multimedia Appendix 1 ) [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Misconceptions or insufficient information about influenza and the vaccine, negative attitudes towards vaccination, level of knowledge and level of perceived risk (Livni, Chodik, Yaari, Tirosh, & Ashkenazi, 2008;Raftopoulos, 2008;Smith et al, 2016aSmith et al, , 2016bZhang, While, & Norman, 2010, 2012b have been identified as influencing their vaccination practices. Nurses represent the largest group of health professionals internationally (World Health Organization, 2016) and have different attitudes about influenza and its prevention compared to physicians (Hollmeyer, Hayden, Poland, & Buchholz, 2009).…”
Section: Introductionmentioning
confidence: 99%